Art Building Design Using Byblos Local Value Themes Approach - Aung Ko Tneth (Newinera Publisher, 2020)
This article discusses the design of an arts building with an approach to the theme of local values. This design is carried out considering the importance of the existence of an art and culture in big cities to boost the local economy and also become an attraction for the tourism sector, as well as the desire of the community to enjoy the beauty of art, as well as the desire of artists to be witnessed and exhibit their works of art. The location that is used as a place for the art building must fill the city spatial planning, where the location of the building that I designed is on Jalan Tanjung Bunga is the central business district, where several supporting facilities such as public transportation, clean water, electricity, telephone network etc., this is the basis for my choosing a location on this flower promontory road. Efforts to increase the attractiveness of the Arts Building by combining traditional Makassar ethnic styles. So that visitors can also find out the typical regional ornaments through this art building. Paying attention to the harmony and balance of design elements in the Arts Building is expected to provide comfort to visitors and organizers of a show.